An update on adult forms of hereditary pheochromocytomas and paragangliomas. Issue 1 (January 2021) - Dariane, Charles; Goncalves, Judith; Timsit, Marc-Olivier; Favier, Judith
Abstract : Purpose of review: Pheochromocytomas and paragangliomas (PPGL) display a strong genetic determinism with 40% of inherited forms. The purpose of this review is to provide an update on current knowledge on adult forms of hereditary PPGL and their management. Recent findings: PPGL are genetically-driven in 70% of cases, with germline and/or somatic mutations identified in more than 20 genes. Although eight new susceptibility genes have recently emerged, mutations on SDHx genes remain the most frequent. In addition to SDHB, mutations in SLC25A11, FH and MDH2 may predispose to a metastatic disease and somatic alterations including TERT and ATRX mutations, and the differential expression on noncoding RNAs are also associated with the occurrence of metastases. The biochemical diagnosis remains the mainstay of functional PPGL and does not differ between hereditary PPGL while the choice of the best nuclear imaging approach is dictated by the tumor type and can be influenced by the presence of a germline mutation (18F-DOPA PET/CT for cluster 2 mutation and 68 Ga-DOTATATE PET/CT for cluster 1 mutation). Summary: A systematic genetic testing and counselling is recommended for all PPGL patients and should lead to conservative surgery and an adapted follow up, in case of hereditary form.